Performance Evaluation of High-Strength Self-Compacting Concrete (SCC) with Nickel Slag as Partial Fine Aggregate Replacement - Muhammad Syarif; James Thoengsal; Randy Setiawan; Shadiqa Pratama Zulfariadi (Structures, Infrastructure, Planning, Implementation, and Legislation, 2026)
The escalating demand for high-performance construction materials has intensified the search for sustainable alternatives to natural aggregates, particularly in the production of High-Strength Self-Compacting Concrete (SCC). This study evaluates the integration of nickel slag from Morowali, Central Sulawesi, as a partial replacement for fine aggregates to address the environmental degradation caused by river sand mining. Utilizing a quantitative experimental design, 48 cylindrical specimens were tested across various substitution levels (0%, 20%, 40%, and 60%) with a consistent water-to-binder ratio of 0.28 and a target characteristic strength of 60 MPa. Rheological parameters were assessed through slump-flow and L-box blocking ratio ( ) tests, while mechanical performance was measured via compressive strength at 7, 14, and 28 days. Results indicate that a 40% substitution threshold represents the optimum balance, yielding a superior characteristic strength of 69.73 MPa a 16.6% enhancement over the control. Rheologically, nickel slag improved fluidity up to 710 mm, although replacements exceeding 40% triggered dynamic instability and segregation, evidenced by an   ratio decline to 0.78. These findings imply that nickel slag is a technically viable reinforcing filler for strategic infrastructure, provided that substitution levels are strictly calibrated. The study concludes that while nickel slag significantly densifies the concrete matrix, industrial adoption requires further standardization of long-term durability metrics. Future research should prioritize the evaluation of creep and chloride resistance in marine environments to ensure structural longevity.